Titanium oxycarbide electrode and preparation method and application thereof

By preparing carbon titanium oxide electrode sheets, the problems of prone to cracking and poor contact after the electrode is large-scaled, and the anode dissolution rate and the service life of the electrode are improved.

CN119751070APending Publication Date: 2025-04-04PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934373.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing carbon titanium oxide electrodes are prone to cracking after being large-scaled, and have poor contact with graphite connectors, resulting in low anode dissolution rate and frequent electrode replacement.

Method used

A preparation method is adopted to mix carbon titanium oxide powder, asphalt and the first binder to form an electrode material, and mix it with carbon aggregate and the second binder to form an electrode paste. The carbon titanium oxide electrode sheet is obtained by molding and sintering to ensure the strength and pore structure of the electrode.

Benefits of technology

The carbon titanium oxide electrode prepared by this method maintains integrity after large-scaleization, avoiding the problems of cracking and poor contact, and improving the anode dissolution rate and the service life of the electrode.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of rare metal extraction, in particular to a titanium oxycarbide electrode and a preparation method and application thereof. The preparation method of the titanium oxycarbide electrode plate comprises the following steps: A) uniformly mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material; uniformly mixing the carbonaceous aggregate with a second binder to obtain an electrode paste; respectively placing the electrode material and the electrode paste in a specific forming mold; b) after compression molding, demolding and drying to obtain a green body; and C) sintering the green body in an inert atmosphere to obtain the carbon titanium oxide electrode plate. When the prepared titanium oxycarbide electrode is used for preparing a large-scale titanium oxycarbide electrode, the problems that the large-scale electrode is easy to crack and the contact between the large-scale electrode and a graphite connecting piece is poor can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare metal refining, and in particular to a titanium oxycarbide electrode, a preparation method and application thereof. Background Art

[0002] Titanium is a metal with very superior properties. It has a series of advantages such as light specific gravity, high specific strength, and good corrosion resistance. It has been increasingly widely used in national defense, chemical industry, metallurgy, medical treatment, industrial and agricultural production and other fields.

[0003] At present, the method for producing titanium metal is magnesium reduction method (Kroll process): first, the titanium raw material is subjected to carbon chlorination to produce titanium tetrachloride, then magnesium metal is used for thermal reduction to obtain titanium sponge, and then the obtained titanium sponge is vacuum distilled to obtain commercial titanium sponge; while magnesium metal is obtained by electrolysis of magnesium chloride, and the chlorine obtained by electrolysis is used to produce titanium chloride. Therefore, the whole production process includes four main parts: chlorination of titanium oxide, thermal reduction of magnesium, vacuum distillation and electrolysis of magnesium chloride. This method has the disadvantages of complicated production process, long cycle, high energy consumption and intermittent production, resulting in excessively high production cost of titanium sponge. The Kroll process is quite mature and there is little room for improvement.

[0004] The USTB method is a method proposed by the University of Science and Technology Beijing to produce pure titanium by anode electrolysis of a soluble solid solution of titanium monoxide / titanium carbide. It uses a carbonaceous reducing agent and a titanium-containing material as raw materials, and is pressed into a shape. After high-temperature vacuum reduction, a titanium oxycarbide solid solution TiCxOy is obtained. After crushing, it is secondary molded and sintered into an electrode, and electrolysis is carried out in a chloride molten salt system containing low-valent titanium ions. During the electrolysis process, the titanium in the solid solution enters the molten salt in the form of ions, and the remaining carbon and oxygen overflow the electrolysis system in the form of CO. In theory, no residual carbon will be produced at the anode, and pure metallic titanium will be deposited on the cathode.

[0005] On this basis, patent application document CN115652371A proposed a method for preparing titanium oxycarbide electrodes, adding a certain proportion of asphalt to the raw materials. The functions of asphalt are: ① Part of the carbon reducing agent; ② Pore-forming agent. The pores formed after the asphalt volatilizes serve as ion channels during the electrolysis process; ③ The unreacted carbon forms a porous carbon skeleton, so that the electrode does not peel off when the gas generated during the electrolysis process flushes the electrode surface. Although the above method has made certain improvements over the USTB method for electrode preparation, it still has problems such as low anode dissolution rate and low titanium oxycarbide content in the electrode, resulting in frequent electrode replacement. When applied to the scale-up test, problems such as easy cracking during the electrode preparation process and poor contact between the electrode and the graphite connector occurred. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a titanium oxycarbide electrode, a preparation method and application thereof. The titanium oxycarbide electrode prepared by the present invention is used to prepare a large titanium oxycarbide electrode, which can avoid the problem of easy cracking of the electrode after being enlarged and poor contact with the graphite connector.

[0007] The present invention provides a method for preparing a titanium oxycarbide electrode sheet, comprising the following steps:

[0008] A) mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material;

[0009] Mixing the carbonaceous aggregate and the second binder to obtain an electrode paste;

[0010] Placing the electrode material and the electrode paste in the forming mold respectively;

[0011] The molding die comprises: a columnar container; and a metal ring disposed at the center of the columnar container; the metal ring is a detachable metal ring;

[0012] Filling the electrode material into the position between the metal ring and the columnar container in the forming mold; filling the electrode paste into the interior of the metal ring, and removing the metal ring;

[0013] B) after compression molding, demoulding, drying, and obtaining a green body;

[0014] C) sintering the green body in an inert atmosphere to obtain a titanium oxycarbide electrode sheet.

[0015] Preferably, in step A), the chemical formula of the titanium oxycarbide is Ti2C x O y , where 0<x<2, 0<y<2;

[0016] The particle size of the titanium oxycarbide powder does not exceed 1000 μm;

[0017] The fixed carbon content of the asphalt is 35% to 45%;

[0018] The particle size of the asphalt does not exceed 3000 μm;

[0019] The first binder is a polyvinyl alcohol solution with a mass concentration of 1% to 2%.

[0020] Preferably, in step A), the mass ratio of the titanium oxycarbide powder, asphalt and the first binder is 65-81:15-25:4-10.

[0021] Preferably, in step A), the carbonaceous aggregate comprises at least one of anthracite, coke, graphite powder, petroleum coke, asphalt coke and electrically calcined anthracite;

[0022] The particle size of the carbonaceous aggregate does not exceed 3000 μm;

[0023] The second binder includes asphalt and / or tar;

[0024] The particle size of the second binder is no more than 3000 μm.

[0025] Preferably, in step A), the mass ratio of the carbonaceous aggregate to the second binder is 80-70:20-30.

[0026] Preferably, in step B), the compression molding pressure is 5 to 80 MPa.

[0027] Preferably, in step C), the sintering includes three stages of temperature increase sintering: firstly, the temperature is increased to 330-370°C for constant temperature sintering, then the temperature is increased to 480-520°C for constant temperature sintering, and finally the temperature is increased to 900-1000°C for constant temperature sintering.

[0028] The present invention also provides a titanium oxycarbide electrode sheet prepared by the preparation method described above.

[0029] The present invention also provides a large-scale titanium oxycarbide electrode, comprising:

[0030] Graphite screw;

[0031] Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray;

[0032] A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw;

[0033] The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet described above.

[0034] The present invention also provides a method for preparing the large-scale titanium oxycarbide electrode as described above, comprising the following steps:

[0035] After a hole is opened in the center of the titanium oxycarbide electrode sheet, it is processed into a thread, and a plurality of the titanium oxycarbide electrode sheets are tightly connected in series by a graphite screw to obtain a large titanium oxycarbide electrode.

[0036] The present invention provides a method for preparing a titanium oxycarbide electrode sheet, comprising the following steps: A) mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material; mixing carbonaceous aggregate with a second binder to obtain an electrode paste; placing the electrode material and the electrode paste in a forming mold respectively; the forming mold comprises: a columnar container; and a metal ring arranged at the center of the columnar container; the metal ring is a detachable metal ring; filling the electrode material in the position between the metal ring and the columnar container in the forming mold; filling the electrode paste in the metal ring and removing the metal ring; B) after compression molding, demolding, drying, and obtaining a blank; C) sintering the blank under an inert atmosphere to obtain a titanium oxycarbide electrode sheet. The titanium oxycarbide electrode prepared by the present invention is used to prepare a large-scale titanium oxycarbide electrode, which can avoid the problem of easy cracking of the electrode after enlargement and poor contact with the graphite connector. After the electrolysis is completed, the titanium oxycarbide is dissolved and the carbon skeleton is retained, so that the shape of the anode remains intact and the anode dissolution rate is high. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a method for preparing a titanium oxycarbide electrode sheet, comprising the following steps:

[0039] A) mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material;

[0040] Mixing the carbonaceous aggregate and the second binder to obtain an electrode paste;

[0041] Placing the electrode material and the electrode paste in the forming mold respectively;

[0042] The molding die comprises: a columnar container; and a metal ring disposed at the center of the columnar container; the metal ring is a detachable metal ring;

[0043] Filling the electrode material into the position between the metal ring and the columnar container in the forming mold; filling the electrode paste into the interior of the metal ring, and removing the metal ring;

[0044] B) after compression molding, demoulding, drying, and obtaining a green body;

[0045] C) sintering the green body in an inert atmosphere to obtain a titanium oxycarbide electrode sheet.

[0046] Regarding step A):

[0047] Mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material;

[0048] Mixing the carbonaceous aggregate and the second binder to obtain an electrode paste;

[0049] Place the electrode material and electrode paste in the molding mold respectively.

[0050] In some embodiments of the present invention, the titanium oxycarbide powder is composed of titanium oxycarbide (Ti2C 0.5 O 0.5 ) is obtained by crushing and screening. The particle size of the titanium oxycarbide powder is not more than 1000 μm; for example, not more than 840 μm; for example, not more than 200 μm.

[0051] In some embodiments of the present invention, the chemical formula of the titanium oxycarbide is Ti2C x O y , wherein 0<x<2, 0<y<2, specifically, x is selected from 0.45, 0.5 or 0.55; y is selected from 0.45, 0.5 or 0.55.

[0052] In some embodiments of the present invention, the fixed carbon content of the asphalt is 35% to 45%, such as 39%. The particle size of the asphalt is no more than 3000 μm; such as no more than 2000 μm; and another example is no more than 200 μm.

[0053] In some embodiments of the present invention, the first binder is a polyvinyl alcohol solution with a mass concentration of 1% to 2%, such as 2%.

[0054] In some embodiments of the present invention, the mass ratio of the titanium oxycarbide powder, asphalt and the first binder is 65-81:15-25:4-10; for example, 75:22.5:6.75, 63:16.8:5.46, 81:22.95:7.29.

[0055] If the asphalt ratio is too high, the strength of the electrode will decrease. Although there will be more pores after sintering, the reduction in strength will cause falling off during electrolysis and physical loss during loading and unloading. If the asphalt ratio is too low, although the strength is higher, the fewer pores will cause a decrease in solubility performance.

[0056] In some embodiments of the present invention, the carbonaceous aggregate is at least one of anthracite, coke, graphite powder, petroleum coke, asphalt coke and electric calcined anthracite. The particle size of the carbonaceous aggregate is not more than 3000 μm; for example, not more than 2000 μm; for example, not more than 1000 μm; for example, not more than 100 μm.

[0057] In some embodiments of the present invention, the second binder is asphalt and / or tar. The particle size of the second binder is no more than 3000 μm, such as no more than 2000 μm, such as no more than 1000 μm, or such as no more than 100 μm.

[0058] In some embodiments of the present invention, the mass ratio of the carbonaceous aggregate to the second binder is 80-70:20-30; for example, 75:25, 70:30, 78:20.

[0059] The forming mold comprises: a columnar container; and a metal ring arranged at the center of the columnar container; the metal ring is a detachable metal ring.

[0060] The metal ring is used as an auxiliary tool in the charging process to separate the electrode paste from the electrode material. After the charging is completed, the metal ring needs to be removed. After removal, the electrode paste and the electrode material are in planar contact with each other. The present invention has no special restrictions on the thickness of the metal ring, for example, the thickness can be very thin or even negligible. In some embodiments of the present invention, the thickness of the metal ring is 0.1 to 1 mm, for example, 0.5 mm.

[0061] The present invention has no special limitation on the bottom diameter of the columnar container, and it can be set as required. In some embodiments of the present invention, the bottom diameter of the columnar container is 240 mm.

[0062] In some embodiments of the present invention, the diameter of the circular surface formed by the metal ring is smaller than the diameter of the circular surface of the cylindrical container, for example, it may be 150 mm.

[0063] In some embodiments of the present invention, the height of the metal ring is the height of the charge, which is greater than or equal to the height of the columnar container. Specifically, the height of the metal ring can be 70 to 100 mm, such as 100 mm or 80 mm. The height of the columnar container can be 70 to 100 mm, such as 100 mm or 70 mm.

[0064] The present invention has no special limitation on the material of the metal ring. In some embodiments of the present invention, the material of the metal ring can be iron, or a ring of other materials, such as plastic, graphite, wood, stone, etc.

[0065] Regarding step B):

[0066] After compression molding, demoulding and drying, a green body is obtained.

[0067] In some embodiments of the present invention, the compression molding pressure is 5 to 80 MPa, such as 15 to 60 MPa.

[0068] In some embodiments of the present invention, the drying temperature is 25°C to the melting point of the asphalt mentioned above, such as 80-120°C, specifically 100°C; the drying time is more than 12 hours, specifically 13 hours.

[0069] Regarding step C):

[0070] The green body is sintered in an inert atmosphere to obtain a titanium oxycarbide electrode sheet.

[0071] In some embodiments of the present invention, the gas forming the inert atmosphere is argon.

[0072] In some embodiments of the present invention, the sintering includes three-stage temperature rising sintering: first, the temperature is raised to 330-370°C for constant temperature sintering, then the temperature is raised to 480-520°C for constant temperature sintering, and finally the temperature is raised to 900-1000°C for constant temperature sintering.

[0073] The heating rate is 8-12°C / min.

[0074] Specific:

[0075] First, the temperature is raised to 350°C for constant temperature sintering, then the temperature is raised to 500°C for constant temperature sintering, and finally the temperature is raised to 950°C for constant temperature sintering.

[0076] The temperature is first raised to 330-370°C at a rate of 8-12°C / min, such as 10°C / min. The sintering time at a constant temperature of 330-370°C is 0.8-1.2h, such as 1h.

[0077] The rate of heating to 480-520°C is 8-12°C / min, such as 10°C / min. The time of constant temperature sintering at 480-520°C is 0.8-1.2h, such as 1h.

[0078] Finally, the rate of heating to 900-1000°C is 8-12°C / min, such as 10°C / min. The time of constant temperature sintering at 900-1000°C is 0.8-1.2h, such as 1h.

[0079] The sintering is performed in an atmosphere furnace.

[0080] After the sintering, the process further includes: cooling along with the furnace.

[0081] The present invention also provides a titanium oxycarbide electrode sheet prepared by the preparation method described above.

[0082] The titanium oxycarbide electrode sheet comprises:

[0083] Carbonaceous aggregate cylinders;

[0084] forming a titanium oxycarbide annulus outside the carbonaceous aggregate cylinder;

[0085] The carbonaceous aggregate cylinder is prepared from electrode paste; and the titanium oxycarbide ring is prepared from electrode material.

[0086] The carbonaceous aggregate cylinder and the titanium oxycarbide ring have the same height, which is the height of the forming mold.

[0087] The present invention also provides a large-scale titanium oxycarbide electrode, comprising:

[0088] Graphite screw;

[0089] Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray;

[0090] A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw;

[0091] The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet described above.

[0092] In some embodiments of the present invention, the disk diameter of the graphite tray is the same as the outer diameter of the titanium oxycarbide electrode sheet.

[0093] As a part of the electrode, the graphite screw is used to connect many electrode sheets together. Due to the weight of the electrode as a whole, the graphite screw needs to have a certain strength, that is, the minimum size of the graphite screw is to bear the weight of the entire electrode without breaking. In some embodiments of the present invention, the diameter of the graphite screw is smaller than the diameter of the cross section of the carbonaceous aggregate cylinder. Specifically, the diameter of the graphite screw can be 100 mm.

[0094] In some embodiments of the present invention, a plurality of the titanium oxycarbide electrode sheets are tightly connected in series using the graphite screw.

[0095] In some embodiments of the present invention, the thread involved in the threaded connection is a standard thread of M60 mm, or a standard thread of M70 mm.

[0096] The present invention also provides a method for preparing the large-scale titanium oxycarbide electrode as described above, comprising the following steps:

[0097] After a hole is opened in the center of the titanium oxycarbide electrode sheet, it is processed into a thread, and a plurality of the titanium oxycarbide electrode sheets are tightly connected in series by a graphite screw to obtain a large titanium oxycarbide electrode.

[0098] In some embodiments of the present invention, the center hole of the titanium oxycarbide electrode sheet is processed into a standard thread of M60mm or M70mm after being opened. The thread of the graphite screw is a standard thread of M60mm or M70mm.

[0099] In the present invention, the titanium oxycarbide electrode sheet is used to prepare the positive electrode material; the large titanium oxycarbide electrode is the positive electrode.

[0100] In order to further illustrate the present invention, the titanium oxycarbide electrode, the preparation method and the application thereof provided by the present invention are described in detail below in combination with the embodiments, but it should not be understood as limiting the protection scope of the present invention.

[0101] Example 1

[0102] 1) Preparation of Titanium Oxycarbide Electrode Sheet:

[0103] 1-1) Titanium carbide (Ti2C 0.5 O 0.5 ) 3000g was crushed and sieved to obtain titanium oxide powder with a size of less than 840μm.

[0104] 1-2) mixing the titanium oxycarbide powder, 900 g of asphalt having a fixed carbon content of 39% (the particle size of the asphalt does not exceed 2000 μm) and 270 g of a first binder (polyvinyl alcohol solution, with a mass concentration of 2%) to obtain an electrode material; in the electrode material, the mass ratio of the titanium oxycarbide powder, the asphalt and the first binder is 75:22.5:6.75;

[0105] 450 g of graphite crumbs (with a particle size not exceeding 1000 μm) and 150 g of asphalt (with a particle size not exceeding 1000 μm) are mixed to obtain an electrode paste; in the electrode paste, the mass ratio of graphite crumbs to asphalt is 75:25;

[0106] Placing the electrode material and the electrode paste in the forming mold respectively;

[0107] The molding die comprises: a columnar container (bottom diameter is 240 mm, height is 100 mm); and a metal ring arranged at the center of the columnar container; the metal ring is a detachable metal ring (iron sheet with a thickness of 0.5 mm and a height of 100 mm); the diameter of the circular surface formed by the metal ring is 150 mm;

[0108] The electrode material is filled in the position between the metal ring and the columnar container in the forming mold; the electrode paste is filled in the interior of the metal ring, and the metal ring is removed.

[0109] 1-3) After compression molding at a pressure of 80 MPa, the mold was removed and dried in an oven at 100° C. for 13 h to obtain a green body.

[0110] 1-4) Sintering the green body in an atmosphere furnace into which Ar gas is introduced:

[0111] First, the temperature was raised to 350°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, then the temperature was raised to 500°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, and finally the temperature was raised to 950°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour;

[0112] After cooling in the furnace, a titanium oxide carbon electrode sheet with a diameter of 240 mm and a height of 50 mm was obtained.

[0113] The titanium oxycarbide electrode sheet comprises:

[0114] Carbonaceous aggregate cylinders;

[0115] forming a titanium oxycarbide annulus outside the carbonaceous aggregate cylinder;

[0116] The carbonaceous aggregate cylinder is prepared from electrode paste; and the titanium oxycarbide ring is prepared from electrode material.

[0117] 2) Preparation of large titanium oxycarbide electrodes:

[0118] After a hole is opened in the center of the titanium oxycarbide electrode sheet, a standard thread of M60 mm is processed and several titanium oxycarbide electrode sheets are tightly connected in series using a graphite screw (the bottom of the graphite screw is fixedly connected to the center of the graphite tray; the thread of the graphite screw is a standard thread of M60 mm) to obtain a large titanium oxycarbide electrode.

[0119] The large titanium oxycarbide electrode comprises:

[0120] Graphite screw; the diameter of the graphite screw is 100 mm;

[0121] Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray;

[0122] A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw;

[0123] The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet described above.

[0124] The disk diameter of the graphite tray is the same as the outer diameter of the titanium oxycarbide electrode sheet.

[0125] 3) Using a large titanium oxide electrode as the anode and a hollow carbon steel rod as the cathode, in a NaCl-KCl-1.0% TiCl n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.08A / cm 2 , cathode current density is 0.2A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 89%.

[0126] Example 2

[0127] 1) Preparation of Titanium Oxycarbide Electrode Sheet:

[0128] 1-1) Titanium carbide (Ti2C 0.45 O 0.55 ) 3000g was crushed and sieved to obtain titanium oxide powder with a size of less than 1000μm.

[0129] 1-2) mixing the titanium oxycarbide powder, 800 g of asphalt with a fixed carbon content of 60% (the particle size does not exceed 2000 μm) and 260 g of a first binder (polyvinyl alcohol solution, with a mass concentration of 2%) to obtain an electrode material; in the electrode material, the mass ratio of the titanium oxycarbide powder, the asphalt and the first binder is 63:16.8:5.46;

[0130] 300 g of graphite crumbs (with a particle size not exceeding 1000 μm), 200 g of petroleum coke, 200 g of coke and 300 g of asphalt (with a particle size not exceeding 1000 μm) are mixed to obtain an electrode paste; in the electrode paste, the mass ratio of graphite crumbs to asphalt is 70:30;

[0131] Placing the electrode material and the electrode paste in the forming mold respectively;

[0132] The molding die comprises: a columnar container (bottom diameter is 240 mm, height is 70 mm); and a metal ring arranged at the center of the columnar container; the metal ring is a detachable metal ring (iron sheet with a thickness of 0.5 mm and a height of 80 mm); the diameter of the circular surface formed by the metal ring is 150 mm;

[0133] The electrode material is filled in the position between the metal ring and the columnar container in the forming mold; the electrode paste is filled in the interior of the metal ring, and the metal ring is removed.

[0134] 1-3) After compression molding at a pressure of 60 MPa, the mold was removed and dried in an oven at 100° C. for 13 h to obtain a green body.

[0135] 1-4) Sintering the green body in an atmosphere furnace into which Ar gas is introduced:

[0136] First, the temperature was raised to 350°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, then the temperature was raised to 500°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, and finally the temperature was raised to 950°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour;

[0137] After cooling in the furnace, a titanium oxide carbon electrode sheet with a diameter of 240 mm and a height of 52 mm was obtained.

[0138] The titanium oxycarbide electrode sheet comprises:

[0139] Carbonaceous aggregate cylinders;

[0140] forming a titanium oxycarbide annulus outside the carbonaceous aggregate cylinder;

[0141] The carbonaceous aggregate cylinder is prepared from electrode paste; and the titanium oxycarbide ring is prepared from electrode material.

[0142] 2) Preparation of large titanium oxycarbide electrodes:

[0143] After a hole is opened in the center of the titanium oxycarbide electrode sheet, a standard thread of M70 mm is processed and several titanium oxycarbide electrode sheets are tightly connected in series using a graphite screw (the bottom of the graphite screw is fixedly connected to the center of the graphite tray; the thread of the graphite screw is a standard thread of M70 mm) to obtain a large titanium oxycarbide electrode.

[0144] The large titanium oxycarbide electrode comprises:

[0145] Graphite screw; the diameter of the graphite screw is 100 mm;

[0146] Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray;

[0147] A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw;

[0148] The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet described above.

[0149] The disk diameter of the graphite tray is the same as the outer diameter of the titanium oxycarbide electrode sheet.

[0150] 3) Using a large titanium oxide electrode as the anode and a hollow carbon steel rod as the cathode, in a NaCl-KCl-1.0% TiCl n (2<n<3) Electrolysis in molten salt system, controlling anode current density to 0.18A / cm 2 , cathode current density is 0.8A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 91%.

[0151] Example 3

[0152] 1) Preparation of Titanium Oxycarbide Electrode Sheet:

[0153] 1-1) Titanium carbide (Ti2C 0.55 O 0.45 ) 3000g was crushed and sieved to obtain titanium oxide powder with a size of less than 200μm.

[0154] 1-2) The carbon dioxide titanium powder, 850 g of asphalt with a fixed carbon content of 50% (the particle size does not exceed 200 μm) and 270 g of a first binder (polyvinyl alcohol solution, with a mass concentration of 2%) are mixed to obtain an electrode material; in the electrode material, the mass ratio of the carbon dioxide titanium powder, the asphalt and the first binder is 81:22.95:7.29;

[0155] 500 g of petroleum coke (with a particle size not exceeding 100 μm), 280 g of coke and 200 g of asphalt (with a particle size not exceeding 100 μm) are mixed to obtain an electrode paste; in the electrode paste, the mass ratio of graphite fragments to asphalt is 78:20;

[0156] Placing the electrode material and the electrode paste in the forming mold respectively;

[0157] The forming mold includes: a columnar container (bottom diameter is 240mm, height is 70mm); and a metal ring arranged in the center of the columnar container; the metal ring is a detachable metal ring (iron sheet with a thickness of 0.5mm and a height of 100mm); the diameter of the circular surface formed by the metal ring is 150mm.

[0158] The electrode material is filled in the position between the metal ring and the columnar container in the forming mold; the electrode paste is filled in the interior of the metal ring, and the metal ring is removed.

[0159] 1-3) After compression molding at a pressure of 40 MPa, the mold was removed and dried in an oven at 100° C. for 13 h to obtain a green body.

[0160] 1-4) Sintering the green body in an atmosphere furnace into which Ar gas is introduced:

[0161] First, the temperature was raised to 350°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, then the temperature was raised to 500°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour, and finally the temperature was raised to 950°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour;

[0162] After cooling in the furnace, a titanium oxide carbon electrode sheet with a diameter of 240 mm and a height of 55 mm was obtained.

[0163] The titanium oxycarbide electrode sheet comprises:

[0164] Carbonaceous aggregate cylinders;

[0165] forming a titanium oxycarbide annulus outside the carbonaceous aggregate cylinder;

[0166] The carbonaceous aggregate cylinder is prepared from electrode paste; and the titanium oxycarbide ring is prepared from electrode material.

[0167] 2) Preparation of large titanium oxycarbide electrodes:

[0168] After a hole is opened in the center of the titanium oxycarbide electrode sheet, a standard thread of M70 mm is processed and several titanium oxycarbide electrode sheets are tightly connected in series using a graphite screw (the bottom of the graphite screw is fixedly connected to the center of the graphite tray; the thread of the graphite screw is a standard thread of M70 mm) to obtain a large titanium oxycarbide electrode.

[0169] The large titanium oxycarbide electrode comprises:

[0170] Graphite screw; the diameter of the graphite screw is 100 mm;

[0171] Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray;

[0172] A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw;

[0173] The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet described above.

[0174] The disk diameter of the graphite tray is the same as the outer diameter of the titanium oxycarbide electrode sheet.

[0175] 3) Using a large titanium oxide electrode as the anode and a hollow carbon steel rod as the cathode, in a NaCl-KCl-1.0% TiCl n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.12A / cm 2 , cathode current density is 1.6A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 93%.

[0176] Comparative Example 1 (low asphalt content in electrode material)

[0177] The difference from Example 1 is:

[0178] In the electrode material, the mass ratio of the titanium oxycarbide powder, the asphalt and the first binder is 75:10:6.75.

[0179] The remaining steps are the same as those in Example 1.

[0180] A large titanium oxide electrode was used as the anode and a hollow carbon steel rod was used as the cathode in a NaCl-KCl-1.0%TiCl n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.08A / cm 2 , cathode current density is 0.2A / cm 2, after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 71%.

[0181] Comparative Example 2 (low asphalt content in electrode paste)

[0182] The difference from Example 1 is:

[0183] In the electrode paste, the mass ratio of graphite chips to asphalt is 85:15. The remaining steps are the same as step 1) in Example 1.

[0184] After the electrode sheet is obtained, a hole is made in the center of the titanium oxycarbide electrode sheet. During the thread processing, the electrode paste is not strong enough after sintering and cannot be processed into a standard thread. After connecting several of the titanium oxycarbide electrode sheets in series, a large titanium oxycarbide electrode is obtained. The large titanium oxycarbide electrode is used as the anode and the hollow carbon steel rod is used as the cathode. n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.08A / cm 2 , cathode current density is 0.2A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 65%.

[0185] Comparative Example 3 (Excessive Molding Pressure)

[0186] The difference from Example 1 is:

[0187] In step 1-3), after compression molding at a pressure of 120 MPa, demolding is performed and drying is carried out in an oven at 100° C. for 13 hours to obtain a green body.

[0188] A large titanium oxide electrode was used as the anode and a hollow carbon steel rod was used as the cathode in a NaCl-KCl-1.0%TiCl n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.08A / cm 2 , cathode current density is 0.2A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 76%.

[0189] Comparative Example 4 (Sintering Temperature Too High)

[0190] The difference from Example 1 is:

[0191] 1-4) Sintering the green body in an atmosphere furnace into which Ar gas is introduced:

[0192] First, the temperature was raised to 420°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour. Then, the temperature was raised to 600°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour. Finally, the temperature was raised to 1100°C at a rate of 10°C / min and sintered at a constant temperature for 1 hour.

[0193] After cooling in the furnace, a titanium oxide carbon electrode sheet with a diameter of 240 mm and a height of 50 mm was obtained.

[0194] A large titanium oxide electrode was used as the anode and a hollow carbon steel rod was used as the cathode in a NaCl-KCl-1.0%TiCl n (2<n<3) Electrolysis in molten salt system, control anode current density to 0.08A / cm 2 , cathode current density is 0.2A / cm 2 , after the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 73%.

[0195] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a titanium oxycarbide electrode sheet, comprising the following steps: A) mixing titanium oxycarbide powder, asphalt and a first binder to obtain an electrode material; Mixing the carbonaceous aggregate and the second binder to obtain an electrode paste; Placing the electrode material and the electrode paste in the forming mold respectively; The molding die comprises: a columnar container; and a metal ring disposed at the center of the columnar container; the metal ring is a detachable metal ring; Filling the electrode material into the position between the metal ring and the columnar container in the forming mold; filling the electrode paste into the interior of the metal ring, and removing the metal ring; B) after compression molding, demoulding, drying, and obtaining a green body; C) sintering the green body in an inert atmosphere to obtain a titanium oxycarbide electrode sheet.

2. The preparation method according to claim 1, characterized in that: In step A), the chemical formula of the titanium oxycarbide is Ti2C x O y , where 0<x<2, 0<y<2; The particle size of the titanium oxycarbide powder does not exceed 1000 μm; The fixed carbon content of the asphalt is 35% to 45%; The particle size of the asphalt does not exceed 3000 μm; The first binder is a polyvinyl alcohol solution with a mass concentration of 1% to 2%.

3. The preparation method according to claim 1, characterized in that: In step A), the mass ratio of the titanium oxycarbide powder, asphalt and the first binder is 65-81:15-25:4-10.

4. The preparation method according to claim 1, characterized in that: In step A), the carbonaceous aggregate comprises at least one of anthracite, coke, graphite powder, petroleum coke, pitch coke and electrically calcined anthracite; The particle size of the carbonaceous aggregate does not exceed 3000 μm; The second binder includes asphalt and / or tar; The particle size of the second binder is no more than 3000 μm.

5. The preparation method according to claim 1, characterized in that: In step A), the mass ratio of the carbonaceous aggregate to the second binder is 80-70:20-30.

6. The preparation method according to claim 1, characterized in that: In step B), the compression molding pressure is 5 to 80 MPa.

7. The preparation method according to claim 1, characterized in that: In step C), the sintering includes three stages of temperature increase sintering: firstly, the temperature is increased to 330-370°C for constant temperature sintering, then the temperature is increased to 480-520°C for constant temperature sintering, and finally the temperature is increased to 900-1000°C for constant temperature sintering.

8. The titanium oxycarbide electrode sheet obtained by the preparation method according to any one of claims 1 to 7.

9. A large titanium oxycarbide electrode, comprising: Graphite screw; Graphite tray; the bottom of the graphite screw is fixedly connected to the center of the graphite tray; A titanium oxycarbide electrode sheet, wherein the titanium oxycarbide electrode sheet has a central opening, and the opening is threadedly connected to the graphite screw; a plurality of the titanium oxycarbide electrode sheets are connected in series by using the graphite screw; The titanium oxycarbide electrode sheet is the titanium oxycarbide electrode sheet according to claim 8.

10. The method for preparing the large titanium oxycarbide electrode according to claim 9, comprising the following steps: After a hole is opened in the center of the titanium oxycarbide electrode sheet, it is processed into a thread, and a plurality of the titanium oxycarbide electrode sheets are tightly connected in series by a graphite screw to obtain a large titanium oxycarbide electrode.